Feasibility of Biophysics Experiments Guide Flipbook on Respiration System Content for Junior High School Student - Andika Febrian; Fairuz Zakirah; Achmad Salehudin; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
The essence of science learning is learning that should be taught more dominantly on exploration of discovery or search for concepts directly by students such as experiments. The lack of experiments guides in school is one of the reasons why practicums are rarely used. This study aims to develop a flipbook-based respiratory system experiment guide. This study uses a 4D development model consisting of define, design, develop, and disseminate stages. The data result of validation was analyzed by quantitative descriptive. Based on the results of the research development on the flipbook product of the respiratory system content practicum guide, the results obtained were feasible in 3 aspects with high categories in didactic aspects and very high categories in construction, technical, and language aspects. This product can be tested to see its effectiveness and practicality in learning at school